1987
DOI: 10.1016/0014-5793(87)80555-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel voltage‐activated channel in the outer mitochondrial membrane

Abstract: Patch-clamp studies of the outer mitochondrial membrane indicate a voltage-dependent increase in conductance for potentials positive relative to the exterior of the mitochondrion.The time course of the conductance changes is consistent with an activation of channels. Voltage pulse experiments suggest that the activation phenomenon corresponds to assembly of the channels from subunits with disassembly occurring after recovery of the original conductance.Effects of temperature and concanavalin A on the voltage-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…The only previous studies on integral liver mitochondria with the patch clamp technique (Kinnally et al 1987(Kinnally et al , 1989bTedeschi et al 1987Tedeschi et al , 1989) yielded a rather different picture than that reported here, for the ionic permeability of the OM. Basically, no single channels but only high intensity currents were recorded.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The only previous studies on integral liver mitochondria with the patch clamp technique (Kinnally et al 1987(Kinnally et al , 1989bTedeschi et al 1987Tedeschi et al , 1989) yielded a rather different picture than that reported here, for the ionic permeability of the OM. Basically, no single channels but only high intensity currents were recorded.…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, the patch clamp technique has been applied to integral mitochondria (Kinnally et al 1987(Kinnally et al , 1989bTedeschi et al 1987Tedeschi et al , 1989, and high intensity currents have been recorded. The lack, under these conditions, of single channel events, was judged an expected phenomenon, as in Neurospora crassa (Freitag et al 1982) and liver (De Pinto et al 1987) mitochondria, the expression of the VDAC is such that a few thousand molecules are likely to be present in a membrane area equal to that of a pipette patch.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that the IMM channel might serve, autonomously or in conjunction with channels present in the outer membrane (Colombini, 1979;Kinnally et al, 1987), in the machinery for the import of cytoplasmically synthesized mitochondrial proteins has already been considered by us (Sorgato et al, 1987) and by others (Thieffry et aI., 1988). The import apparatus seems to lie in those regions where the two mitochondrial membranes are juxtaposed (Hartl et al, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the existence of a second ionic channel in the outer membrane was suggested by the properties of the porin-deficient mutants [31], the growth of which was unaffected under aerobic conditions. It was also suggested in 'patch-clamp' experiments on giant mitochondria [3], where a second conductance was induced by voltage jumps. A cationic channel has been observed by reconstitution in bilayers of detergent-solubilized outer membranes of porin-deficient yeast mutants [4].…”
Section: Discussionmentioning
confidence: 99%